4,4′-(Propane-1,3-diyl)dipyridinium tetrachloridonickelate(II) - Ju-Ping Qu; Zhong-Xiang Du (Acta Crystallographica Section E, 2009)
The title compound, (C13H16N2)[NiCl4] or (H2bpp)·NiCl4 [bpp is 1,3-bis(4-pyridyl)propane], is isostructural with its already reported Cu, Zn and Hg analogues. The structure consists of a doubly charged (H2bpp)2+ cation and a tetrahedral [NiCl4]2− dianion. Both pyridyl N atoms are protonated and form a (H2bpp)2+ cation which adopts an anti–anti conformation with a dihedral angle of 6.287 (7)° between the pyridyl rings. The two pyridyl N atoms are both involved in strong N—H...Cl hydrogen bonds, which link both units into a dimer.